2008
DOI: 10.3748/wjg.14.6473
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin deficiency enhances colorectal carcinogenesis and liver tumor formation induced by azoxymethane in mice

Abstract: AIM:To investigate the causal relationship between hypoadiponectinemia and colorectal carcinogenesis in in vivo experimental model, and to determine the contribution of adiponectin deficiency to colorectal cancer development and proliferation. METHODS: We examined the influence of adiponectin deficiency on colorectal carcinogenesis induced by the administration of azoxymethane (AOM) (7.5 mg/kg, intraperitoneal injection once a week for 8 wk), by using adiponectin-knockout (KO) mice. RESULTS: At 53 wk after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Furthermore, colon adenoma formation is promoted by the deficiency of adiponectin and colonic epithelial cell pro-J Med Biochem 2014; 33 (2) 139 liferation is increased in animals fed a high-fat diet (13). In addition to these results, a significant decrease was observed in AMPK phosphorylation in intestinal epithelial cells of adiponectin-knockout mice compared with the control group (19).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, colon adenoma formation is promoted by the deficiency of adiponectin and colonic epithelial cell pro-J Med Biochem 2014; 33 (2) 139 liferation is increased in animals fed a high-fat diet (13). In addition to these results, a significant decrease was observed in AMPK phosphorylation in intestinal epithelial cells of adiponectin-knockout mice compared with the control group (19).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, the induction of colorectal cancer in wild-type and adiponectin knockout mice resulted in an increase in the number, volume and aggressiveness of, as well as in the occurrence of metastasis from, colorectal tumors in adiponectin knockout mice when compared to wild-type mice [267]. Moreover, COX-2 expression in the colorectal tumors of adiponectin-deficient mice was higher relative to wild-type mice.…”
Section: Cancermentioning
confidence: 96%
“…Moreover, COX-2 expression in the colorectal tumors of adiponectin-deficient mice was higher relative to wild-type mice. Given that COX-2 is a well-established pathogenic factor in colorectal carcinogenesis, those findings further suggest that adiponectin may play a protective role against colorectal cancer development [267]. Working on two independent case-control studies, Kaklamani et al [268] recently reported that individuals with the adiponectin rs266729 (-11365 C ?…”
Section: Cancermentioning
confidence: 97%
“…Experimentally, colorectal tumours induced by azoxymethane were histologically more progressive with greater frequency in adiponectin-knockout mice 71 . At present, however, little is known about the molecular mechanism of enhanced tumour formation and growth in adiponectin deficiency and further studies are needed.…”
Section: Cancermentioning
confidence: 99%